2006
DOI: 10.1021/ie051167+
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of the Influence of Temperature and Pressure on the Flow Pattern in Cyclones

Abstract: A three-dimensional computational fluid dynamics (CFD) model of flow through cyclones was developed to obtain the pressure drop and flow profiles. The CFD results agreed very well with the experimental data obtained by Bohnet (Chem. Eng. Process. 1995, 34, 151) and Boysan et al. (Inst. Chem. Eng. Symp. Ser. 1983, 69, 305). CFD simulations were also performed at various flow rates, temperatures, and pressures. A fictitious fluid was used to observe the separate effects of density and viscosity on the flow patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Wang et al (2006), Wan et al (2008) and Raoufi et al (2009) have demonstrated the use of CFD in reasonably predicting the tangential velocity under varied conditions. The temperature also has an effect on the tangential velocity (Shi et al, 2006). A minor decrease is noticed at the area of the inner vortex with increasing the temperature.…”
Section: Tangential Velocitymentioning
confidence: 98%
“…Wang et al (2006), Wan et al (2008) and Raoufi et al (2009) have demonstrated the use of CFD in reasonably predicting the tangential velocity under varied conditions. The temperature also has an effect on the tangential velocity (Shi et al, 2006). A minor decrease is noticed at the area of the inner vortex with increasing the temperature.…”
Section: Tangential Velocitymentioning
confidence: 98%
“…Fluidic systems like vortex tube, [1][2][3] cyclone separators, [4][5][6] swirl tube, 7 hydrocyclones, 8 vortex whistle, swirl combustors, 9 and the vortex diode, [10][11][12] are widely used in various engineering applications. The performance of these devices is largely dominated by the confined turbulent vortex/vortices, due to the tangentially entering fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the operating pressure on the flow field in a single cyclone separator is analyzed (Xiong et al, 2005;Shi et al, 2006). The density strongly affects the flow field.…”
Section: Pressure Drop Of Multicyclone Separatormentioning
confidence: 99%